Development of Three-Tier Diagnostic Test to Measure Misconceptions of Grade 5 Students about Fractions - Ariza Fitriani Safira; Harun Harun (JETL (Journal of Education, Teaching and Learning), 2024)
This research developed a measuring instrument in the form of a three-tier diagnostic test to measure students' misconceptions in fraction material in grade V. This research aims to determine (1) the validity, reliability, and item characteristics of the three-tier diagnostic test and (2) the level of misconceptions of grade V elementary school students in Pontianak. This research used quantitative approach and test development model by Mardapi, that has nine steps. The subjects were fifth-grade students in Pontianak City, and the developed test instruments focused on addition-subtraction of fractions, each with two sets of questions A and B. The instrument were analyzed for content and construct validity, reliability, and item characteristics based on IRT using Partial Credit Model (PCM). The results show that the developed test instrument demonstrated strong content and construct validity. Reliability analysis shows high reliability, with Cronbach's Alpha values >0,7. Item fit analysis reveal that 91% and 73% were fit, therefore the unfit items were fixed or eliminated. The analysis of misconceptions shows that 39.52% of students do not understand the concept of fractions’ addition and subtraction, and 29.09% experienced misconceptions. Additionally, 12.61% have false positives, and 8.97% have false negatives. Only 6.30% understood the concept correctly, and 3.52% guessed correctly or understood but had doubts. Generally, the final test instrument demonstrated good validity, reliability and item qualities.